If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4q + 8p = x Reorder the terms: 8p + 4q = x Solving 8p + 4q = x Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-4q' to each side of the equation. 8p + 4q + -4q = -4q + x Combine like terms: 4q + -4q = 0 8p + 0 = -4q + x 8p = -4q + x Divide each side by '8'. p = -0.5q + 0.125x Simplifying p = -0.5q + 0.125x
| 17.50x+3.50=125x | | X=17+(-1.5y) | | -3(3p-3)=-18 | | Sc+8-4c-2-c= | | 2400+.02x=400+.1x | | -2+X^2=-2 | | 5x-(6x+5)=6x-26 | | 1250-16t^2=0 | | -4-8y=-20 | | 0.30+6y=300forx | | 2x^2+1x=0 | | y=ax^3 | | 4x-3(x-2)=20 | | 7=u-11 | | -4(2.5)-8y=24 | | -6x+28=-6 | | 17.50*3.50x=125 | | 225m+450=1800 | | 1800+.5x=800+.7x | | 225m+450=1800 | | 1800+.5x=800+.7x | | -.43(3)-2= | | 4-Y=-20 | | 8(r+4)=-7(-5-r) | | 12n+3=13n-6 | | 14-6.2x(-3+-7)= | | -4x-8(4)=24 | | 4(c+0)=2x+6 | | 148=-8(-6+2x)-4x | | 3x(-8)-2x(-5)= | | px-t=k | | 6.8=15.8+3b |